Provision of Complementary Foods for Breastfeeding (MP-ASI) on the Growth of 0-6 Months Babies at Hanna Kasih Clinic in 2019 - Nurdiana Manurung (Institute of Computer Science (IOCS), 2019)
The provision of supplementary food to infants in Indonesia is still not appropriate for their age, especially in rural areas. Infants 0-6 months are only given breast milk (ASI), while additional food is given over the age of 6 months. Information about the importance of breastfeeding needs to be developed so that mothers understand and understand the relationship between complementary feeding (MP-ASI) on the growth of infants 0-6 months.